Freezing Regimens and Gel Carrier Composition Influence Safety of Saccharomyces boulardii Immobilized Yeast Cells - Vysekantsev, Igor; Martsenyuk, Valentyna; Buriak , Iryna; Gurina, Tatyana (Problems of Cryobiology and Cryomedicine, 2021)
The effect of DMSO and sucrose added to alginate gel on the viability of immobilized Saccharomyces boulardii yeast cells after rapid and slow cooling to –196 °C has been studied. Thermomechanical analysis revealed the inflection of phase transitions corresponding to each component of the solutions when cooling those of 1% sodium alginate contained 20% sucrose or 5% DMSO down to –196 °C. Phase transitions caused by the presence of DMSO and sucrose in sodium alginate solutions were observed at lower temperatures than in impurity-free sodium alginate solution. In experiments to study the viability of free and immobilized yeast cells after freezing, it was found that the highest viability of free cells suspended in solutions of sodium alginate, DMSO, sucrose, and the cells immobilized in gel granules, was provided by a cooling rate of 1 deg/min followed by immersion in liquid nitrogen. After adding DMSO and sucrose separately to the alginate gel, as well as their combinations, the viability of immobilized cells increased. The maximum viability of immobilized cells was found in gel granules, which contained the following combinations of cryoprotectants: 5% DMSO and 10% sucrose, 5% DMSO and 20% sucrose, 10% DMSO and 10% sucrose and 10% DMSO and 20% sucrose. Probl Cryobiol Cryomed 2021; 31(4): 343–352